Pembentukan Tanggung Jawab Siswa Melalui Daring pada Pembelajaran PPKn - Khonila Khonila (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2022)
This research aims to find out how the implementation of e-learning in shaping responsible characteristic of 9th grade students of SMPN 5 Sungailiat in PPKn learning and to know what efforts are made to shape the responsible characteristic of 9th grade students of SMPN 5 Sungailiat through e-learning in PPKn learning.The research method used in this research is descriptive qualitative research method. This research started from Maret to Mei 2021. Data collection techniques are done by observation, documentation, and interviews. Interviews were conducted with informants, namely 10 9th grade students from Class A, B, and D, and a key informant, which was the PPKn teacher of SMPN 5 Sungailiat. Also carried out the confirmation process with an expert, the Character Lecturer. Data analysis was done by data reduction, data display, and conclusion drawing/verification. The conclusion of this research is 9th grade students of SMPN 5 Sungailiat throughout did the e-learning in PPKn learning, carry it out properly be responsibility even though there are still obstacles. The teachers' efforts to shape the responsible characteristic of 9th grade students of SMPN 5 Sungailiat through e-learning in PPKn learning are to give assignments and set the time for collection, provide motivation and appreciation, and give sanctions to students who violate.